John and Jacqueline Kennedy: politics, culture and the „new frontier“ of clothing - Simona Čupić (University of Belgrade, 2016)
Jacqueline Kennedy’s style is one of the mainstays of the history of fashion and popular culture, as well as contemporary politics. John Kennedy’s way of dressing garnered much less attention. Even though, at first glance, not as interesting as the first lady’s “fashion sense”, the president’s style was no less thought-out. If, however, we view the changes in clothing as social changes and a determinant of various kinds of social differentiation: marital status, sex, occupation, religious and political affiliation, the way in which the Kennedys were presented to the public becomes more interesting – from the (carefully planned) photos and appearances to art and culture. Having in mind that the 1960s were a time when the appropriation of popular and fictional came back into modern art, and that general changes inherent in the new lifestyle, as well as a layered image of American internal politics, and the cold war map of the world, the carefully thought-out image of the presidential couple can be viewed as a specific kind of metaphor for a complicated time.